Partnerships Involved in Public Health Testing for Zika Virus in Florida, 2016. (November 2019) - Heberlein-Larson, Lea; Gillis, Leah D.; Morrison, Andrea; Scott, Blake; Cook, Mary; Cannons, Andrew; Quaye, Elesi; White, Stephen; Cone, Marshall; Mock, Valerie; Schiffer, Jarad; Lonsway, David; et al.
The emergence of Zika virus in the Americas in 2015 and its association with birth defects and other adverse health outcomes triggered an unprecedented public health response and a demand for testing. In 2016, when Florida exceeded state public health laboratory capacity for diagnostic testing, the state formed partnerships with federal and commercial laboratories. Eighty-two percent of the testing (n = 33 802 of 41 008 specimens) by the laboratory partners, including Florida's Bureau of Public Health Laboratories (BPHL; n = 13 074), a commercial laboratory (n = 19 214), and the Centers for Disease Control and Prevention (CDC; n = 1514), occurred from July through November 2016, encompassing the peak period of local transmission. These partnerships allowed BPHL to maintain acceptable test turnaround times of 1 to 4 days for nucleic acid testing and 3 to 7 days for serologic testing. Lessons learned from this response to inform future outbreaks included the need for early planning to establish outside partnerships, adding specimen triage strategies to surge plans, and integrating state and CDC information systems.